Longitudinal PET studies of mGluR5 in FXS using an FMR1 knockout mouse model - Afshar Sepideh; Lule Sevda; Yuan Gengyang; Qu Xiying; Pan Chuzhi; Whalen Michael; Brownell Anna-Liisa; Mody Maria (Translational Neuroscience, 2022)
Fragile X syndrome (FXS) is a monogenic disorder characterized by intellectual disability and behavioral challenges. It is caused by aberrant methylation of the fragile X mental retardation 1 (FMR1) gene. Given the failure of clinical trials in FXS and growing evidence of a role of metabotropic glutamate subtype 5 receptors (mGluR5) in the pathophysiology of the disorder, we investigated mGluR5 function in FMR1 Knockout (FMR1-KO) mice and age- and sex-matched control mice using longitudinal positron emission tomography (PET) imaging to better understand the disorder. The studies were repeated at four time points to examine age- and disease-induced changes in mGluR5 availability using 3-fluoro-[18F]5-(2-pyridinylethynyl)benzonitrile ([18F]FPEB). We found that the binding potential (BP) of [18F]FPEB was significantly lower in the KO mice in mGluR5-implicated brain areas including striatum, cortex, hippocampus, thalamus, and olfactory bulb. The BP also changed with age, regardless of disorder status, increasing in early adulthood in male but not in female mice before decreasing later in both sexes. The difference in mGluR5 availability between the FMR1-KO and control mice and the change in BP in the KO mice as a function of age and sex illustrate the nature of the disorder and its progression, providing mechanistic insights for treatment design.